2006
DOI: 10.1016/j.clinph.2006.06.755
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus context determines whether non-target stimuli are processed as task-relevant or distractor information

Abstract: Objective: The P300 event-related brain potential (ERP) was elicited using a visual three-stimulus oddball paradigm (standard 0.70, target 0.15, non-target 0.15) to examine how target/standard stimulus context affects non-target processing.Methods: Target/standard discrimination difficulty (easy or difficult) and non-target /target similarity (similar or dissimilar) were manipulated orthogonally. Participants (N = 13) were instructed to respond to each infrequent target stimulus by pressing a button.Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 33 publications
12
27
0
Order By: Relevance
“…ERP and fMRI studies suggest that frontal attentional mechanisms govern responsivity to contextual novelty (Bledowski et al, 2004a;Kiehl et al, 2001;Kirino et al, 2000;Suwazono et al, 2000), which also imply top-down control (cf. Dien et al, 2004;Ranganath and Rainer, 2003;Sawaki and Katayama, 2006, 2007. The degree of attentional focus, therefore, appears to govern P3a generation whereas the stimulus context contributes to the P3b.…”
Section: Theoretical Considerationsmentioning
confidence: 91%
See 1 more Smart Citation
“…ERP and fMRI studies suggest that frontal attentional mechanisms govern responsivity to contextual novelty (Bledowski et al, 2004a;Kiehl et al, 2001;Kirino et al, 2000;Suwazono et al, 2000), which also imply top-down control (cf. Dien et al, 2004;Ranganath and Rainer, 2003;Sawaki and Katayama, 2006, 2007. The degree of attentional focus, therefore, appears to govern P3a generation whereas the stimulus context contributes to the P3b.…”
Section: Theoretical Considerationsmentioning
confidence: 91%
“…Katayama and colleagues reported that unique visual stimulus distracter designs (e.g., red squares on either side of the target stimulus) that "capture attention" from the target/standard task produce robust P3a components (Sawaki and Katayama, 2006, 2007. The nature of the distracter disruption has led to the direct assessment of ERP components linked to early stimulus feature evaluation, which engages the selective attention garnered by both stimulus context and task difficulty (Kimura et al, 2008a(Kimura et al, , 2008b(Kimura et al, , 2008cSawaki and Katayama, 2008b).…”
Section: Stimulus Context and Attentional Focusmentioning
confidence: 95%
“…Similar late positivity can be recorded for rare nontarget stimuli of the three-stimulus oddball task (frequent 'standard', frequent 'target' and infrequent 'nontarget' stimuli) [20] . P3a appears as an anterior (frontal or central) component in many studies with various paradigms, but in the case of easy target/standard discrimination and nontarget/target similarity in the oddball paradigm, posterior P3a-like components were also recorded [4] . According to recent results, P3a is also elicited by target stimuli [21] .…”
Section: Introductionmentioning
confidence: 99%
“…The amplitude and scalp distribu-tion of these components are determined by the relationships between the characteristics of the eliciting stimuli and the ongoing cognitive activity. As an example, the P3a ERP component of a task-irrelevant stimulus is larger and has more anterior distribution in demanding discrimination tasks than in easier tasks [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Rare, task relevant stimuli reliably produce the well-known P300 oddball ERP (Fabiani et al, 1987;Donchin and Coles, 1988;Johnson, 1988;Sawaki and Katayama, 2006) and this occurs for both types of rare stimuli (probes and targets) in this GKT paradigm. Of particular relevance is the oddball response to those rare items (probes) that the person attempts to conceal; in a sense, a recollection process gives the person away due to a memory trace activation making the event significant and salient.…”
Section: Introductionmentioning
confidence: 94%